2016
DOI: 10.1021/acs.chemmater.6b02634
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Acoustic Cavitation Initiation by Porous Nanoparticles: Toward Nanoscale Agents for Ultrasound Imaging and Therapy

Abstract: Ultrasound is widely applied in medical diagnosis and therapy due to its safety, high penetration depth, and low cost. In order to improve the contrast of sonographs and efficiency of the ultrasound therapy, echogenic gas bodies or droplets (with diameters from 200 nm to 10 µm) are often used, which are not very stable in the bloodstream and unable to penetrate into target tissues. Recently, it was demonstrated that nanobubbles stabilized by nanoparticles can nucleate ultrasound responsive microbubbles under r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 66 publications
1
98
0
Order By: Relevance
“…In addition, the progress and location of therapy may be monitored by imaging the generated bubbles during ablation using common ultrasound imaging equipment. Recently, we [34, 35] and others [3640] showed that hydrophobic micro/nanoparticles dispersed in aqueous media can generate bubbles when subjected to an ultrasound pulse with peak negative pressures of a few MPa. Under reduced acoustic pressures, air stabilized at the hydrophobic interface act as nucleation sites for bubble growth.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the progress and location of therapy may be monitored by imaging the generated bubbles during ablation using common ultrasound imaging equipment. Recently, we [34, 35] and others [3640] showed that hydrophobic micro/nanoparticles dispersed in aqueous media can generate bubbles when subjected to an ultrasound pulse with peak negative pressures of a few MPa. Under reduced acoustic pressures, air stabilized at the hydrophobic interface act as nucleation sites for bubble growth.…”
mentioning
confidence: 99%
“…The bubble grows outside the particle from the contribution of the dissolved gases and water vapor, followed by collapse. [34, 37, 38] Such bubble generating micro/nanoparticles were applied to improve the contrast of ultrasound images by our group, [34, 35] and as well as to enhance the drug delivery efficiency by others. [37] Also, Zhao, et al, [40] recently used hydrophobic MSNs to kill cancer cells by reactive oxygen species generation under continuous low energy ultrasound (LEUS) insonation rather than pulsed HIFU.…”
mentioning
confidence: 99%
See 3 more Smart Citations